Tendencii razvitija dissertacionnych issledovanij v sfere fiziceskoj kul'tury i sporta v našej strane - Baranov, V. N.; Shustin, B. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The paper examines the dynamics of the number and topics of dissertations performed in our country in areas related to physicalculture and sports: mass physical culture and mass sports, high-performance sports and the preparation of a sports reserve, physical culture and sports management system, training, advanced training and retraining physical culture. The bulk of theses were prepared for pedagogical specialties. In addition, the preparation of dissertations on this topic was carried out in a number of branches of science, primarily biological, medical, psychological, etc. It was shown that in the post-Sovietperiod the total number of dissertations increased significantly. At the same time, the growth dynamics of the number of dissertations in different areas is not the same. At the same time, the analysis performed shows a steady decline in the last decade of the number of dissertations prepared in the field of physical culture and sports, especially doctoral ones.